The influence of whistleblowing system toward fraud prevention - Maulida, Windy Yulian; Bayunitri, Bunga Indah (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to determine the implementation of whistleblowing system and fraud prevention, and to find out how the whistleblowing system affects fraud prevention at the Jabar Banten Central Bank in Bandung. Research Methodology: This study used the explanatory method and simple linear regression analysis. The program used was SPSS Version 19.00. Results: The whistleblowing system affected fraud prevention by 54.3%. Limitation: The study is limited to the role of the whistleblowing system and fraud prevention. Contribution: The results of this study contribute to improving the application of the whistleblowing system and preventing fraud. Keywords: Whistleblowing system, Fraud prevention